Efficient ternary organic photovoltaic device with a non-halogenated solvent via synergistic inhibiting charge recombination and regulating morphology. Issue 8 (2nd February 2023) - Liu, Xingpeng; Peng, Yichun; Liang, Zezhou; Wang, Limin; Han, Shenghui; Dou, Zheng; Lu, Xubin; Tong, Junfeng; Liu, Jiangang; Li, Jianfeng
Abstract : Ternary strategies are essential for the development of high-performance organic photovoltaic (OPV) devices. Similarly, green and environmentally friendly solvent processing in OPV devices is imperative for commercial applications. Abstract : Environmentally friendly and efficient organic photovoltaic (OPV) devices play an essential role in commercial applications. Herein, the PM6:TBFCl50-BDD:IT-4F-based ternary device was fabricated using the non-halogenated solvent o -xylene ( o -XY), and a third component (TBFCl50-BDD) that is similar to the PM6 structure. It was found that the addition of 20 wt% TBFCl50-BDD enhanced the crystallinity of the ternary blend film and significantly improved the charge transport and collection ability, which could effectively suppress trap-assisted recombination and bimolecular recombination. Meanwhile, the introduction of TBFCl50-BDD accelerated the diffusion of excitons to the donor–acceptor interface and promoted exciton dissociation. Ultimately, the ternary device achieved a power conversion efficiency (PCE) of 12.8%, which is higher than that of the PM6:IT-4F binary device (11.8%).